Insecticides Efficacy to Control the Neotropical Peanut Burrower Bug Cyrtomenus mirabilis (Perty, 1830) (Hemiptera: Cydnidae) Under Laboratory Conditions - Michelotto, Marcos D.; Reis, Aline D. P.; Rodrigues, Renato M.; Rincão, Rodolfo O.; Andrade, Daniel J.; Schwertner, Cristiano F.; Godoy, Ignácio J. (Entomological Communications, 2023)
In this study, we evaluated the effectiveness of insecticides sprayed by contact as well as seeds treatment for controlling the burrower bug Cyrtomenus mirabilis (Perti, 1830) (Hemiptera: Cydnidae) under laboratory conditions. In the first experiment, the insecticides were sprayed onto the insects (direct contact). Insect mortality evaluation started 24h after insecticide application and repeated every two days up to 20 days. In the second experiment, peanut seeds were treated with insecticides. The mortality of insects was evaluated at 10, 15, and 20 days after installation. The mixture of fipronil and alpha-cypermethrin in direct contact was the most efficient treatment to control nymphs and adults of C. mirabilis. Regarding the seed treatment, fipronil was the most efficient for controlling adults of C. mirabilis while for nymphs, all insecticides were highly effective.